Influence of limestone as pre-treatment for sustainable acid mine drainage water quality management in Tanzania - Marwa, Alexander; Sweya, Lukuba Ngalya (Journal of Degraded and Mining Lands Management, 2024)
Acid Mine Drainage (AMD) is a major environmental problem due to low pH, high sulphate content, and dissolved metals. The aim of this study was to investigate the potential of limestone materials for the primary treatment of AMD water. Different doses of limestone were used in this study in the ratio of 0 g/1,000 mL as control, 20 g/1,000 mL, 40 g/1,000 mL, 60 g/1,000 mL, 80 g/1,000 mL, 100 g/1,000 mL, 200 g/100 mL (limestone/AMD) in a batch experiment of 1,500 mL plastic container. The results showed that the pH of AMD water improved to 8.6 at a dose of 100 g/1,000 mL, and the sulphate concentration decreased from 2,277 mg/L to 506 mg/L at a dose of 200 g/1,000 mL. The removal of Fe, Cu, Zn, Mn, and Ni at 200 g/1,000 mL was 99%, 92%, 68%, 96%, and 99%, respectively. The results of this study also showed that the Mn content decreased slowly as the limestone dosage increased. In addition, this study showed that limestone is a good neutralizing agent for increasing the pH of AMD water and reducing sulphate and dissolved metal concentrations. The results of this study indicated that limestone is suitable as a primary treatment agent for AMD water treatment in gold mines in Tanzania.